PERAN PERGURUAN TINGGI DALAM PENGEMBANGAN AGROWISATA BERKELANJUTAN UNTUK MENEKAN KERUSAKAN LINGKUNGAN DI SAMBLONG, JEMBRANA, BALI - I Wayan Sumandya; A.A Istri Mirah Dharmadewi; I Kadek Yudha Pranata; Made Agus Wijaya; I Putu Pasek Suryawan; Ni Putu Sri Ratna Dewi; I Gusti Ayu Mira Ardanantya; I Gusti Ketut Adnyani; Tiurma Silvia Leonita; Desak Made Echa Herawati; I Putu Darma Yuda (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2024)
The development of sustainable agrotourism in Samblong, Jembrana, Bali, is a strategic solution to mitigate environmental degradation. This community service program aims to optimize the role of higher education institutions in supporting sustainable agrotourism development through participatory methods, training, research, and the implementation of environmentally friendly technologies. The method used involves a participatory approach, where local communities are engaged in the planning and implementation of the program. Higher education institutions provide training in agrotourism management, sustainable agricultural practices, and digital marketing, as well as technical assistance in using eco-friendly technologies. The results of this community service show an increased understanding among the community about the concept of sustainable agrotourism and the application of organic waste management technologies. Research conducted by the university yielded environmental data used as the foundation for long-term land management planning. Additionally, there was an improvement in the community's skills in promoting agrotourism digitally, directly impacting income growth. Collaboration between universities, local communities, and regional governments also succeeded in strengthening synergy in managing natural resources. Overall, this program has successfully reduced the rate of environmental degradation and improved the welfare of the community in Samblong.